Simulação de faltas de alta impedância em sistemas de distribuição de energia elétrica - Bacil, Gustavo Galeazzi (2020)
When a protection system acts as a result of a permanent fault, several consumers will remain without electricity for the time spent locating and restoring the system to its normal and safe operating state. The reliability of the system has direct proportionality with the time of maintenance of the maintenance teams, thus, the shorter the fault location time, the more reliable the system is classified. High impedance faults are characterized by having a sufficiently high impedance value to compromise the operation of conventional overcurrent relays, fuses, and fault locating techniques, for example. The associated fault current values are smaller than those representing the nominal behavior of the protected circuit and are caused by the contact of an energized conductor to the ground, a tree, a structure or any equipment, for example. Unlike short-circuits, which involve expressive current values and therefore are easier to detect, high impedance faults present a challenge for protection and operation of the power system. These cause very little damage to the electrical power system equipment, however, failure to detect them entails serious risks to the safety of consumers as well as becoming the source of ignition for fires. This research aims to improve an existing computational model of high impedance fault, using data from oscillographs raised from practical testes performed, in order to reproduce characteristics that approximate the real ones generated in the occurrence of the defect type in question , and in addition, to implement model obtained in a real electricity distribution system previously modeled, in order to analyze its behavior.